APLIKASI PEMANFAATAN LIMBAH INDUSTRI BATU COBEK DI DESA TOYOMARTO SEBAGAI BATU HIAS GABION ATAU BROJONG - Abadi, Machrus (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Topographically, Toyomarto Village, Singosari District, Malang Regency, is included in the category of highland areas with an altitude of ± 622 meters above sea level (masl). In 1981, the mortar and mortar handicrafts became the livelihood of residents in Petung Wulung hamlet, Toyomarto village, Singosari sub-district. The purpose of this service is to provide waste benefits as an economic value for local residents. Therefore, the community service team planned a concept to use mortar waste as gabion and brojong stones. In addition, increasing the economic value of the waste will also increase the attractiveness of using mortar waste as a decoration in Toyomerto village in beautifying the environment. In this community service activity 4 (four) gabion or brojong designs were produced. Among them are cylindrical, tubular, and semi-spherical or circular with a conical top for planting media and plants. It also has its own offer for the villagers apart from being a decoration for the environment, as well as a typical souvenir from the village of Toyomarto. Plants that are chosen besides their aesthetics are those that can survive indoors and outdoors and do not require much water or a continuous watering process, for example plants of the Agavesiklok, Portulaca Grandiflora, Cactus and so on. The results of the implementation of this program were well received by the community and could improve the economy of Toyomarto Village.